Approval and RegiWstration of Marriage Agreements Created During Marriage in Practice (Constitutional Court Decision No. 69/PUU-XIII/2015) - Adrianus Jeffri Shandietrysno; Brigita Cindy Wibisono; Gwyneth Lorraine Sajogo (Budapest International Research and Critics University, 2022)
This journal examines the provisions for making and recording marriage agreements found in Indonesia's three legal instruments, namely Law Number 1 of 1974 concerning Marriage (Marriage Law), which was followed by Constitutional Court Decision Number 69/PUU-XIII /2015 and Civil Registration Number 472.2/5876 regarding Marriage Agreement Reporting. The Constitutional Court's reading of Article 29(1) of the Marriage Law enables a variety of interpretations regarding the ratification and recording of marriage agreements. By doing a literature review and using legal resources that can aid in obtaining the results of the discussion in answering the problem formulation, the research method used will lead to a juridical-normative type of research. The ratification of the marriage agreement during the marriage is investigated, as well as whether the Notary's confirmation is sufficiently binding.